Analisis Faktor-Faktor Yang Berpengaruh Terhadap Kepuasan Pelanggan Martabak Padang Pak Jee - Sari, Miranti Kusuma; Kasih, Yulizar (Universitas Multi Data Palembang, 2024)
The purpose of this research is to examine partially and simultaneously the effect of product quality, service quality, and price on customer satisfaction of Martabak Padang Pak Jee. The sample used was 220 samples. Data collection methods with a questionnaire using a Likert measurement scale. The research approach uses a quantitative approach. Non probability sampling is a technique for sampling with purposive sampling method. The results showed that partially the independent variable had an effect on the dependent variable. Simultaneously, the independent variable affects the dependent variable.